SAKHAITOIDES, A NEW EARLY TRIASSIC AMMONOID GENUS - Ermakova S.P. (My University, 1999)
A new genus Sakhatoides is established based on Upper Induan material from Northeastern Asia. The morphogenesis of the major structural elements of its shell and the phylogeny of the new genus are studied. Two species of the genus Sakhatoides: S. allarensis (Dagys et Ermakova, 1996) and S. verkhoyanicus (Popow, 1976) are described.
Keywords: Triassic; Mesozoic::Triassic; Мезозой::Триасовая